Comparative efficacy of High-Flow Nasal Cannula (HFNC) versus Continuous Positive Airway Pressure (CPAP) in Preventing Bronchopulmonary Dysplasia (BPD) among Preterm Neonates - Wajid Iqbal; Shaukat Zaman; Javeria Iqbal; Faiz Alam; Muhammad Khalid Khan; Samina Shams Alam (Pakistan Journal of Health Sciences, 2026)
Bronchopulmonary dysplasia (BPD) remains a major cause of respiratory morbidity in preterm infants requiring respiratory support. Non-invasive ventilation strategies such as nasal continuous positive airway pressure (CPAP) and high-flow nasal cannula (HFNC) are commonly used, but evidence comparing their effectiveness in preventing BPD remains limited, particularly in low- and middle-income settings. Objectives: To compare HFNC and CPAP as primary non-invasive respiratory support in preterm neonates